Olive Fruit Extracts Supplement Improve Antioxidant Capacity via Altering Colonic Microbiota Composition in Mice - Wang, Mengyu; Zhang, Shunfen; Zhong, Ruqing; Wan, Fan; Chen, Liang; Liu, Lei; Yi, Bao; Zhang, Hongfu (Frontiers in Nutrition, 2021)
Oxidative stress, one of the most common biological dysfunctions, is usually associated with pathological conditions and multiple diseases in humans and animals. Chinese olive fruit (Canarium album L.) extracts (OE) are natural plant extracts rich in polyphenols (such as hydroxytyrosol (HT)) with antioxidant, anti-hyperlipidemia, and anti-inflammatory potentials. This study was conducted to investigate the antioxidant capacity of OE supplementation and its related molecular mechanism in mice. Experimental mice were treated with 100 mg/kg body weight (BW) OE for 4 weeks, then the antioxidant and anti-inflammatory capacities were examined. The results showed that OE supplement significantly increased the serum antioxidative enzyme activities of T-AOC, SOD, GSH-Px, and CAT and decreased the serum MDA level, indicating that OE treatment enhanced the antioxidant capacity in mice. qPCR results showed that the transcriptional expression of antioxidant SOD1, CAT, Gpx1, and Gpx2 were significantly downregulated in the small intestine (jejunum and ileum) after OE administration. Furthermore, TNF-α and IL-1β as pro-inflammatory cytokines were significantly decreased, which confirmed its antioxidation and anti-inflammatory capacities with OE administration. Using amplicon sequencing technology, 16S rRNA sequencing results showed that OE supplement significantly increased the colonic Firmicutes/Bacteroidetes ratio, which also has a negative correlation with the serum MDA level and positively correlated with serum GSH-Px activity through Pearson correlation analysis. In summary, this study showed that treatment with 100 mg/kg BW polyphenol-rich OE could alter colonic microbiota community associated with improvement of antioxidant capacity in mice.